Thermal processing of canned ready-to-drink soybean (Glycine max Linn.) milk - Mallari, Maria Teresa Atanacio
The yelloow variety of soybean (Glysine max L.) was used in the establishment of a thermal process for canned soybean milk. The most acceptable formulation was determined using three levels of sugar (5, 7, and 9%) and three water extraction ratios (1:8, 1:9, and 1:10). The 9% sugar level and the soybean to water extraction ratio of 1:9 was chosen based on the highest mean score for general acceptability, the objective to produce a 'refreshing' rink that is neither "too thick nor too thin", and a product that would contain higher total solids. Heating characteristics of soybean milk in 307 x 409 (2T) cans processed at a retort temperature of 250°F for 20 minutes were determined. The required process was determined using the formula or mathematical method. Based on the thermal resistance parameters of the reference organism C. sporogenes (PA 3679), D-value of 1.5 minutes and z-value of 18 and the heating parameters of soybean milk. The calculated process time (B) was approximately 15 minutes at process temperature of 250°F. Calculated processing time of 15 minutes at retort temperature of 250°F was applied on a bench scale production run to determine the adequacy of the process. Cut-out tests and sensory evaluation were done after two and three weeks of storage, respectively. Based on the tests the process schedule was found to be adequate making product commercially sterile. In terms of organoleptic attributes and general acceptability, the product was acceptable with panel scores ranging from "like slightly" to "like moderately".